Electromechanical wear of the contact wire–current collecting insert pair in electric transport systems - Kovtun, O.S.; Polishchuk, A.O. (Problems of Tribology, 2026)
The article considers the processes of current collection and wear in the sliding electrical contact system "contact wire - current collection insert" of a trolleybus. It is shown that the destruction of contact surfaces has a complex electromechanical nature and is caused by the simultaneous action of mechanical, electrical and thermal factors. The main mechanisms of electrical and mechanical wear of contact elements are analyzed, in particular, electroerosion, abrasive, fatigue and molecular-mechanical wear. The influence of contact pressure, current collector speed, traction current magnitude and properties of contact pair materials on the intensity of destruction of surface layers is considered. It is shown that the uneven distribution of current in the contact zone leads to local overheating of the surface and the formation of electric arcs, which accelerate the electroerosion destruction of contact elements. It is established that the formation of a thin graphite film on the surface of the contact wire can partially reduce the friction coefficient and wear intensity. The results obtained can be used to increase the durability of current-collecting elements of electric transport and optimize their operating modes.